MAINTENANCE MANAGEMENT ANALYSIS OF INDUCE DRAFT FAN (IDF) EQUIPMENT OF COAL FIRE POWER PLANT (CFPP) LONTAR USING LIFE CYCLE COST ANALYSIS APPROACH - Winda Nur Cahyo; Nova Ardyanto (Spektrum Industri, 2020)
To maintain the performance to optimalization operating at Coal Fire Power Plant (CFPP) the reliability of power plant equipment needs to be maintained especially on critical equipment. Based on CFPP failure data during 2012 – 2017, one of the critical equipment is the Induce Draft Fan (IDF).  The Journal will analyze the reliability, availability and maintainability for the IDF equipment with the approach of Life Cycle Cost Analysis (LCCA). Using the IDF equipment failure data during 2012 - 2017 which is processed using Minitab 17 application with Weibull Analysis method, the results obtained the mean value (µ) for MTTF and shape parameters (β) and scale parameters (η) for calculation  MTTR. That data combined with the hours of annual routine maintenance periods for each unit, used to calculate the operating and maintenance (O&M) hours of IDF in a year and then combined with operational cost data so the total O&M costs for the IDF during 15 years period obtained. Consider with assumptions for the calculation, the final results can provide input for management to making appropriate maintenance decisions.Based on analysis data, MTTF and MTTR values for IDF 1A is 10,726.6 hours and 43.84 hours, IDF 1B is 4,891.07 hours and 5.35 hours, IDF 2A is 5961.44 hours and 75.45 hours, IDF 2B is 7,047.26 hours and 163.70 hours, IDF 3A is 5,059.77 hours and 220.86 hours then IDF 3B is 7,218.89 hours and 101.14 hours. The results of LCCA approach for 15 years obtained the lowest total maintenance cost is IDF unit 1 of 527.68 billion.